JUSTIFICATION OF DIRECTIONS FOR IMPROVING THE ORGANIZATION OF MEDICAL CARE FOR PATIENTS WITH COVID-19 AND METABOLIC DISORDERS - Tetiana S. Gruzieva; Olena Ya. Antonyuk (Клінічна та профілактична медицина)
Introduction. Between 2015 and 2023, Ukraine’s healthcare system faced significant disruptions due to the COVID-19 pandemic, full-scale war, and ongoing economic instability. Worsening demographic indicators, increasing inpatient mortality, and declining accessibility of medical care underscore the need for a comprehensive analysis to develop effective strategies for adapting the healthcare system to current conditions, challenges, and threats.